A field guide to community based adaptation - Magee, Tim
"The world's poor will be the most critically affected by a changing climate--and yet their current plight isn't improving rapidly enough to fulfil the UN's Millennium Development Goals. If experienced development organizations are finding it difficult to solve decades-old development problems, how will they additionally solve new challenges driven by climate change? A Field Guide to Community Based Adaptation illustrates how including community members in project design and co-management leads to long-lasting, successful achievement of development and adaptation goals.This field guide provides a system of building block activities for staff on the ground to use in developing and implementing successful adaptation to climate change projects that can be co-managed and sustained by communities. Based on years of experience in 129 different countries, the field guide uses a step-by-step progression to lead readers through problem assessment, project design, implementation, and community take over. The book equips development staff with all the tools and techniques they need to improve current project effectiveness, to introduce community based adaptation into organizational programming and to generate new projects. The techniques provided can be applied to broad range of challenges, from agriculture and drainage problems, to health concerns, flood defences and market development. The book is supported by a user-friendly website updated by the author, where readers can download online resources for each chapter which they can tailor to their own specific projects.This practical guide is accessible to all levels of development staff and practitioners, as well as to students of development and environmental studies. "--